Study on the Use of AI Technology in Completing Theoretical Assignments for Fashion Design Students - Siti Kholifah; Esin Sintawati; Agus Hery Supadmi Irianti; Nurul Aini; Hariani Aprilia (ETDC: Indonesian Journal of Research and Educational Review, 2026)
This study was motivated by the increasing use of Artificial Intelligence (AI) technology in learning. The development of this technology raises the question of whether the use of AI technology is more likely to have a positive impact or a predominantly negative impact. The purpose of this study is to describe the use of AI technology in competing theoretical assignments by students in the Fashion Design Education undergraduate program. This study uses a descriptive quantitative approach. This research involved a population of 173 Fashion Design Education undergraduate students from the 2023-2024 cohort, and a sample of 121 respondents was obtained through purposive sampling. The research instrument was a questionnaire that had been tested for validity and reliability. Data analysis used tabulation and frequency distribution to describe trends in AI utilization in several aspects. The results show that the use of AI technology in completing theoretical assignments range from moderate to very high category, indicating that AI was used quite intensively by students to support their academic activities. Thus, it can be concluded that AI technology serves as a tool used by students to support the completion of theoretical assignments.